PENGEMBANGAN E-MATERI BERBASIS COURSELAB MATAPELAJARAN IPS POKOK BAHASAN MENGHARGAI JASA DAN PERANAN TOKOH PERJUANGAN DALAM MEMPERSIAPKAN KEMERDEKAAN INDONESIA KELAS V SDN TAPAK PANEKAN MAGETAN - Saiman Saiman; Rini Apriyanty (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2013)
E-matter that is structured science area information set for study that is presented in the form of electronic that make easy student to accessing matter that taught by teacher, so that easier student to study matter that given. Courselab ingredient composer’s soft apparatus teaches multimedia to e-learning powerful and easy used. Courselab this be alternative that can be used teacher to learning e-matter for student especially Class V. This research aims to detect feasibility e-matter study that developed based on validation result to be used in social science study at Class V elementary school. Research method that used R & D. R & D method that used to produce certain product, and test product effectiveness. This method is used to produce and test e-matter based on Courselab. Study media based on Courselab social science that developed proper used to support study social science main criticism appreciates service and struggle figure part in prepare Indonesia independence, because tested the feasibility by media expert and study matter expert with proper result.